Structural studies with novel ruthenium anticancer agents. - Soon, Cin Huang. (2010)
In this study, we aim to obtain the crystal structure of the ruthenium based anticancer agents which will provide us a better understand on the drug’s mechanism of action. Two ruthenium based drugs, RuCl2(η6-p-cymene)-(PTA), (PTA = 1,3,5-triaza-7-phosphaadamantane) or RAPTA-C and Hind[trans-RuCl4(ind)2] (ind = indazole) or KP1019 were chosen to react with different DNA oligonucleotides. Weak non-covalent binding of RAPTA-C towards the DNA oligonucleotides is observed. KP1019 shows a tendency for stronger covalent binding towards the DNA oligonucleotides but requires high drug to DNA molar ratios. Due to its transient binding, RAPTA-C is not suitable for use in crystallizations. Crystals of the KP1019 adducted oligonucleotides could not be obtained from the condition that gave crystals for unadducted oligonucleotides. Hence, more screens are needed to obtain optimized conditions for the growth of KP1019-derivirtized oligonucleotides.